Appendicular invagination in a pre-school child; a case-report and literature review - De la Rosa-Campos, Dyanne (2023)
Intestinal invagination occurs when an intestinal segment is introduced into another segment. The appendicular presentation is less common and affects predominantly infants. The diagnosis is corroborated during the surgical intervention which consists of de-invagination followed by surgical removal of the appendix, if the latter is not possible then a wide resection or right hemicolectomy is indicated. We present the case of a 4-year-old girl who attended with a history of abdominal pain, anorexia, vomiting and fever; an abdominal ultrasound showed intestinal agglomeration and a rounded mass. The surgical findings included appendicular invagination that affected the cecum, the lesion was resected until the ascending colon. An ileostomy was performed, the anatomopathological findings indicated necrosis of the appendix. Three months later the normal intestinal transit was restored. Appendicular intussusception has non-specific symptoms and could be mortal in Peru. A detailed clinical history may help in diagnosing and offering proper treatment.